A Deluge of Affects: Critical Encounters in The Body Remembers When the World Broke Open - Darias-Beautell, Eva (International Journal of English Studies, 2023)
This article examines Elle-Máijá Tailfeathers and Kathleen Hepburn’s film The Body Remembers When the World Broke Open (2019) through the lens of materialist and feminist affect theories as they intersect with critical Indigeneity. It investigates how the film produces two parallel and conflicting reactions in the viewer, for whom “ugly feelings” (Ngai, 2007), such as failure, embarrassment, pity or shame, compete with an overwhelming and often frustrated need for empathy and compassion.